2018
DOI: 10.1038/s41598-018-28062-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mild Blast Traumatic Brain Injury on Cognitive- and Addiction-Related Behaviors

Abstract: Traumatic brain injury (TBI) commonly results in cognitive and psychiatric problems. Cognitive impairments occur in approximately 30% of patients suffering from mild TBI (mTBI), and correlational evidence from clinical studies indicates that substance abuse may be increased following mTBI. However, understanding the lasting cognitive and psychiatric problems stemming from mTBI is difficult in clinical settings where pre-injury assessment may not be possible or accurate. Therefore, we used a previously characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 100 publications
2
21
2
Order By: Relevance
“…These increases were also observed in both single and repeated blast exposure models of mTBI (i.e., single in (Lim et al, 2015), repeated in the present study), consistent with other preclinical studies finding elevated intake of drugs of abuse using different models of TBI (Mayeux et al, 2015;Weil et al, 2016;Merkel et al, 2017b;Vonder Haar et al, 2018). It should be noted that in our studies using cocaine and oxycodone ((Muelbl et al, 2018) and the present study), food self-administration was conducted prior to drug self-administration. This was done to determine if injury affected operant conditioning and to ensure that rats had a similar ability to perform the task prior to drug exposure.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These increases were also observed in both single and repeated blast exposure models of mTBI (i.e., single in (Lim et al, 2015), repeated in the present study), consistent with other preclinical studies finding elevated intake of drugs of abuse using different models of TBI (Mayeux et al, 2015;Weil et al, 2016;Merkel et al, 2017b;Vonder Haar et al, 2018). It should be noted that in our studies using cocaine and oxycodone ((Muelbl et al, 2018) and the present study), food self-administration was conducted prior to drug self-administration. This was done to determine if injury affected operant conditioning and to ensure that rats had a similar ability to perform the task prior to drug exposure.…”
Section: Discussionsupporting
confidence: 91%
“…These tests were conducted without food restriction and with a limit of 64 reinforcers earned per day to minimize overtraining effects. We saw no differences between injured and non-injured rats in drug seeking during extinction sessions following cocaine self-administration (Muelbl et al, 2018) or oxycodone self-administration under an FR-1 schedule of reinforcement in the present study. Thus, the contribution of prior association between the Rats underwent repeated blast injury (n = 11) or sham exposure (n = 12) once a day for 3 days, after which they were implanted with a jugular catheter, and then trained for food self-administration under an FR-1 schedule of reinforcement.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…To date, few studies have examined voluntary drug self-administration after TBI. However, these studies largely converge on the conclusion that animals with injury self-administer more drug, or escalate their intake more quickly, across both alcohol and cocaine ( Lim et al , 2015 ; Mayeux et al , 2015 ; Weil et al , 2016 ; Vonder Haar et al , 2018 ), although such self-administration may depend upon injury type, severity, and substance, as one group found no changes in cocaine intake after blast injury ( Muelbl et al , 2018 ), while others have seen increased alcohol intake after blast ( Lim et al , 2015 ), and increased cocaine after mild or severe focal injury ( Vonder Haar et al , 2018 ). Moreover, studies have found interesting subgroup differences within TBI animals with regard to acquisition of drug self-administration ( Lim et al , 2015 ; Vonder Haar et al , 2018 ), in which some TBI rats show faster acquisition of drug self-administration than others, suggesting potential biological or behavioral mediators of resilience that warrant investigation.…”
Section: Special Considerations For Pharmacotherapy Following Traumatmentioning
confidence: 99%